Future Service in Industry 5.0: Survey Paper - Umar Al Faruqi (Jurnal Sistem Cerdas, 2019)
With the rapid development of technology in the digitalization era, Industry 4.0 became a terminology that became a reference for research and development in the field of technology in various sectors. This continues to trigger all people to develop technology to enable better utilization in facilitating human life. Society 5.0 is an idea that explains the revolution in people's lives with the development of the fourth industrial revolution. The concept that wants to be presented is how there is a revolution in society that both utilizing technology and also considering humanities aspects. Some sectors of work and needs are beginning to enter digitalization that utilizes Artificial Intelligence, Big Data, Robotics, Automation, Machine Learning, and the Internet of Things.